Peripheral Neuromodulation and Opioid Sparing Strategies for Mitigating Perioperative Pain in the Stabilization and Hardware Removal of Complex Trimalleolar Fractures: A Case Report - Bi Mo; Sandra Sacks; Jerry Markar (Clinical Case Reports)
ABSTRACT Individualized opioid‐free perioperative management, combining dual continuous peripheral nerve catheters targeting the popliteal sciatic and adductor canal nerves, non‐opioid pharmacologic agents, and adjunctive neuromodulation, offers robust multimodal analgesia. This approach supports both ORIF and hardware removal in complex trimalleolar fractures while preserving function, reducing opioid‐related risks, and promoting faster recovery.